Design and Implementation of Canteen Order Management System - Avanish Shukla; Prem Vishwakarma; Bhalendu Singh; Harshkumar Thakur; Rohini Rathod (Research & Review: Electronics and Communication Engineering, 2026)
The increasing demand for fast and efficient food services in institutional canteens, such as those in colleges, universities, and corporate organizations, often results in long waiting queues, order-processing delays, and customer dissatisfaction during peak hours. Traditional manual ordering methods are time-consuming and can lead to errors in order handling and payment management. To address these challenges, this project presents the design and implementation of a smart canteen order management system that enables customers to place food orders via a user-friendly web application, eliminating the need to stand in physical queues. The proposed system is developed using the MERN Stack, comprising MongoDB, Express.js, React.js, and Node.js, providing a robust, scalable, and efficient platform for real-time order processing and data management. When a customer places an order, the system automatically generates a unique token number that serves as an order identifier. Customers can track the status of their orders and receive notifications when their food is prepared and ready for collection. The system also provides an administrative interface for canteen staff to manage menu items, monitor incoming orders, update order statuses, and maintain transaction records. By digitizing the ordering process, the proposed solution significantly reduces waiting times, improves operational efficiency, minimizes human errors, and enhances the overall customer experience. The system offers a practical and cost-effective approach for modernizing canteen services and supporting seamless food order management during high-demand periods.